(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Buchholzia coriacea, taken by elderly, has phytochemicals that have neuro-active metabolites, and the folklore documented its use in neuro-behavioral despairs. Previous study in our laboratory shows that methanol extracts of Buchholzia coriacea (MEBC) seeds possess antidepressant-like potentials in laboratory rodents. This present study was conducted to investigate the probable mechanism(s) of action by which MEBC potentiates its effects using laboratory rodents. Involvements of serotonergic, cholinergic and adrenergic systems were studied using Forced Swimming Test (FST) and Tail Suspension Test (TST) models of behavioral despair. Antagonists which including: Prazosin, an alpha-1-adrenergic receptor blocker (62.5 μg/kg, i.p.), metergoline, a 5HT2 receptor blocker (4 mg/kg, i.p.) and atropine, a -muscarinic cholinergic receptor blocker (1mg/kg i.p.) were administered before effective dose of MEBC (50mg/kg). Also, the hippocampi of the animals were studied for changes in neuronal density using Nissl Staining. Our findings showed that mobility was reversed in animals pre-treated with atropine, prazosin, and metergoline significantly (P˂0.05), showing a possible involvement of the corresponding systems. However, there was a significant reduction in immobility time (P<0.001) during FST after chronic administration of the MEBC. The hippocampus showed no significant changes (P<0.05) in neuronal density. In conclusion, MEBC probably potentiates its antidepressant-like potentials via the cholinergic, adrenergic and partly by serotonergic systems.